A universal route to N-coordinated metals anchored on porous carbon nanosheets for highly efficient oxygen electrochemistry - Ren, Jin-Tao; Yuan, Zhong-Yong (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Rational design and preparation of economical, high-efficiency, and robust electrocatalysts for the reversible oxygen reduction and evolution reactions to substitute noble-metal electrocatalysts are significantly vital for the development of electrocatalytic energy conversion technologies. Metal modified N-doped carbon materials have attracted tremendous interest due to the evidently improved activities and fascinating features, whereas the development of facile and efficient fabrication methodologies is still highly challenging. Herein, we elaborately developed a reliable and scalable graphitic carbon nitride (g-C 3 N 4 )-templated method to prepare uniformly dispersed N-coordinated metal (M = Fe, Co, Ni, Cu, Mn, Mo and Sn) species in porous carbon nanosheets (M-N-C PCSs) using cost-effective and sustainable polyacrylonitrile (PAN) as a heteroatom precursor and carbon source. With the assembly of sufficiently distributed N-coordinated metal species, and advanced porous nanosheet architectures, the as-synthesized M-N-C PCSs, especially Fe-N-C PCSs, exhibit an outstanding catalytic efficiency for both oxygen reduction and evolution reactions in an alkaline medium, even competing with the state-of-the-art Pt/C catalysts and recently reported highly active non-noble electrocatalysts, thus possessing an ability to work as an air cathode for rechargeable Zn-air batteries with a large peak power density and high long-term durability. This reported synthesis approach will provide novel but facile guidance to the exploration and preparation of various porous carbon materials with an outstanding efficiency for diverse energy systems. Highly porous carbon nanosheets with N-coordinated metals are rationally developed and show outstanding electrocatalytic oxygen reduction and oxygen evolution performance.